P16 loss facilitate hydroquinone‐induced malignant transformation of TK6 cells through promoting cell proliferation and accelerating the cell cycle progression. Issue 8 (1st May 2021) - Luo, Hao; Zhai, Lu; Qiu, Weifeng; Liang, Hairong; Yu, Lei; Li, Yuan; Xiong, Mengyun; Guo, Jiaying; Tang, Huanwen
Abstract: The p16 INK4A is a multifunction gene that includes regulation of the cell cycle, apoptosis, senescence and tumor development. However, the effects of p16 in hydroquinone‐induced malignant transformation of TK6 cells remain unclear. The present study aimed to explore whether p16 loss facilitate malignant transformation in TK6 cells. The results demonstrated that p16/Rb signal pathway was suppressed in hydroquinone‐induced malignant transformation of TK6 cells. We further confirmed that p16 loss stimulated cell proliferation, and accelerated cell cycle progression in vitro and in vivo. The immunoblotting analysis indicated that p16 regulated cell cycle progression via Rb and p53. Therefore, we conclude that p16 is involved in HQ‐induced malignant transformation associated with suppressing Rb and p53 which resulting in accelerating the cell cycle progression.